2012
DOI: 10.1371/journal.pone.0034944
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media in a New Mouse Model for CHARGE Syndrome with a Deletion in the Chd7 Gene

Abstract: Otitis media is a middle ear disease common in children under three years old. Otitis media can occur in normal individuals with no other symptoms or syndromes, but it is often seen in individuals clinically diagnosed with genetic diseases such as CHARGE syndrome, a complex genetic disease caused by mutation in the Chd7 gene and characterized by multiple birth defects. Although otitis media is common in human CHARGE syndrome patients, it has not been reported in mouse models of CHARGE syndrome. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…However the specific anomalies described vary somewhat between the models. With respect to the eyes for example, our zebrafish models show an underdeveloped lens, the previously described zebrafish models show retinal disorganization, the frog models develop colobomas, and the mouse models present with keratoconjunctivitis sicca (7, 13, 24, 39). The underlying basis for these differences is not known, but interestingly, this phenotypic variability is highly reminiscent of that seen among human patients with CHARGE syndrome and warrants further study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However the specific anomalies described vary somewhat between the models. With respect to the eyes for example, our zebrafish models show an underdeveloped lens, the previously described zebrafish models show retinal disorganization, the frog models develop colobomas, and the mouse models present with keratoconjunctivitis sicca (7, 13, 24, 39). The underlying basis for these differences is not known, but interestingly, this phenotypic variability is highly reminiscent of that seen among human patients with CHARGE syndrome and warrants further study.…”
Section: Discussionmentioning
confidence: 80%
“…To date, zebrafish, frogs, and mice have been used to study the role of CHD7 in development (7, 8, 13, 23, 24, 38, 39). The overall phenotype and the organ systems affected in the chd7 morphants reported here are consistent with those previously observed in the other models (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Cilia dysfunctions have been implicated in a number of conditions, including neonatal respiratory distress, chronic nasal congestion, bronchiectasis and sinusitis, and chronic otitis media with effusion67810111263646566. Despite the significant association and likely contributory role of cilia in OM671112636667, the most common childhood disease, only a sparse number of studies examined ciliation in the epithelium that lines the middle ear cavity and thus have provided only a partial understanding of ciliation in the middle ear13141617686970. Moreover, the orientation of the cilia, which is the structural feature of cilia critical to their motility output and clearance function, has not even been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability studies have shown that genetic factors can play an important role in otitis media susceptibility, but few contributing genes have been identified in human populations [1]. In contrast to human studies, a growing number of mouse mutations have been identified that manifest a high incidence of otitis media, including Eya4 , Tlr4 , p73 , MyD88 , Fas , E2f4 , Plg , Fbxo11 , Evi1 [1,2], Sh3pxd2b [3], Rpl38 [4], Isl1 [5], Chd7 [6], Lmna1 [7], Phex [8], Oxgr1 [9], Tgif1 [10], and Mcph1 [11]. The wide diversity of these genes and their mutant pathologies, including craniofacial abnormalities with Eustachian tube malformations and innate immune response defects, underscores the complex nature of otitis media.…”
Section: Introductionmentioning
confidence: 99%